Assessment of ?-projection concept and fracture cavitation - Baldan, A.; Tascioglu, E. (Springer, 2008)
The empirical approach to creep, termed theta-projection concept, is applied to the constant-load data of conventionally cast nickel-base superalloy IN-100 at constant temperature (900 degrees C). The normal creep curves, obtained at various initial stresses (sigma(A) = 200-400 MPa), could be accurately represented by this concept. The change in creep curve shape with stress from tertiary dominated to primary dominated view is presented by the change in the ratio of primary (epsilon(p)) and tertiary strain (epsilon(t)) components to rupture strain (epsilon(R)). It is predicted that failure in the present creep conditions is dominated by the GB cavitation and the growth of the cavities is controlled by the coupled GB diffusion and power-law creep mechanism. In an attempt to provide a physical significance to theta-parameters, it is found that the internal structural variable theory and continuous GB cavitation account well, with suitable assumptions, for the theta description of primary and tertiary creep curves, respectively.
Materials Science and Technology Conference and Exhibition (MS&T'07) -- SEP 16-20, 2007 -- Detroit, MI
Keywords: High-Temperature Creep; Life Prediction; Low Strain; Rupture; Behavior; Growth; Metals; Steels; Copper; Times